Estimation of the share of women in the number of students of higher educational institutions: data by regions of Russia - Pinkovetskaia, Iuliia (Perspectivas em Diálogo: Revista de Educação e Sociedade, 2022)
The purpose of our study was to evaluate the indicators characterizing the gender structure of students of higher education institutions in the regions of Russia. These indicators were the proportion of women among students studying at higher education institutions in 2017-2020. The study used official statistical information for 82 regions of Russia. We used the density functions of the normal distribution as models. The results of the computational experiment showed that, on average, there was a feminization of higher education in the regions, since the share of women in the number of students was in the range from 52% to 55%. At the same time, in the majority (68%) of regions, the number of female students exceeded the number of male students. The proposed methodological approach and the results obtained have a scientific novelty, since the assessment of the territorial features of the gender structure of students in the regions of Russia has not been carried out before.